PERSPECTIVE OF EDUCATIONAL AND SOCIAL CHANGES: EDUCATIONAL FREEDOM - Malgozhata Kaminska (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article represents an attempt to interpret the concept of freedom of education in the midst of discussions about the value and manifestations of freedom and democracy. It has been proven that nurturing freedom is, in a certain way, an element of nurturing democracy, and the role of education as a leading factor in the formation of relations between freedom and coercion has been analyzed. Freedom of education is both a purpose and a means of caring for the longevity and quality of a democratic society. Two concepts of freedom («freedom from», negative freedom, and «freedom for», positive freedom) have been considered from the point of view of the philosophical and psychological dimension. The article presents a kind of illustration for the phenomena that accompany the educational and social changes taking place in the Polish reality today. Their negative manifestations include a hidden educational program without self-dependence, independence of thought and critical thinking; development and approval of official educational plans and programs; «tyranny of the majority» and non-observance of the rights of the minority; ideologization of education and science. The signaled phenomena of controlled freedom, elitist or fictitious freedom, provided to themselves, devoid of critical reflection and awareness of their consequences, can significantly reduce the quality of education, and therefore weaken the entire educational system and the level of a democratic society. It has been concluded that the pace of real democratic change in education lags behind social and cultural change; despite the expansion of the educational space and the scope of available information, certain tendencies towards educational and ideological subjection continue to persist in Poland.